LONG-TERM ASSESSMENT OF FIRE-INDUCED CARBON LOSS IN SOUTHEAST ATLANTIC FOREST - Baião, Cheila Flávia de Praga [UNESP]; Massi, Klécia Gilli [UNESP]; de Sousa Junior, Wilson Cabral (Sociedade de Investigacoes Florestais (SIF), 2024)
Fires threaten tropical forests such as Atlantic Forest in Brazil, compromising the ecosystem service of carbon stock. However, there is a literature gap regarding these studies in these ecosystems. Therefore, we conducted this analysis in different land use and land cover (LULC) classes, considering seasonality and topographic, hydrological, anthropogenic and fire variables correlations, during 2000-2020. The InVEST Carbon model was used, applied to carbon biomass pre-fire and pos-fire, based on field work and linear regression, weighted by pre-and post-fire NBR spectral index. The results, in 21 years, revealed a total loss after fire of 55.7GgC (43%), and of these, 79% is in old-growth Ombrophilous dense. In general, fire negatively impacts the carbon stock of native forests by an average of 38% (ranging from 19.9% to 69.1%, depending on phytophysiognomy and seasonality), Eucalyptus plantations by 87.1%, high-altitude grasslands by 79.5% and pasture in 90.4%. Burn frequency and severity as well as distance from rivers and roads were significantly correlated with carbon loss. A small portion of this biome has shown a high potential for fire-induced carbon loss, indicating a danger for the whole Atlantic Forest conservation and to international agreements commitments.
AVALIAÇÃO DE LONGO PRAZO DA PERDA DE CARBONO INDUZIDA PELO FOGO NA MATA ATLÂNTICA DO SUDESTE
Keywords: Carbon stock; Ecosystem; Fire; InVEST